The Effect of Giving Temulawak (Curcuma zanthorrhiza) Flour on The Productivity of Puyuh Bird Eggs - Sukriani, Ni Luh; Sarjuni, Sri (FAPETKAN UNTAD, 2021)
This study aims to determine the effect of ginger flour on the productivity of quail eggs. This research has been carried out in the animal husbandry department of the Faculty of Animal Husbandry and Fisheries, Tadulako University, South Sibalaya Village, Tanambulava District, Sigi Regency, Central Sulawesi Province, for 8 weeks, August 8 - October 3, 2020. The research material used 100 livestock. Layer phase female quails were obtained from previous research and quail seeds were obtained from the quail breeding group in Palu City, Central Sulawesi Province. This study used a completely randomized design (CRD) with 5 treatments and 4 replications, the levels of use of ginger flour were as follows: (P0: 0%; P1: 0.5%; P2: 1%; P3: 1.5%; and P4 : 2%). The variables observed were ration consumption (g), percentage of egg production (%) and ration conversion. The results of the analysis of variance showed that the use of ginger flour in the ration had no significant effect (P> 0.05) on ration consumption and ration conversion, and had a very significant effect (P <0.01) on egg production. Conclusion: from the results and discussion, it can be concluded that the best result is the provision of 1.5% ginger flour in the ration in terms of the percentage of egg production produced.